The nth term is 9n-2
n2
7n - 3
It is: 25-7n
The nth term = 9n-2
tn = n2
Un = 25 - 7n
Formula for nth termTn = a + (4n - 1) {where a is the first term and n is natural number}
3n^2 - n + 1
The nth term is 7n-3 and so the next term will be 39
The given sequence is an arithmetic sequence with a common difference of 7 (18-11=7, 25-18=7, and so on). To find the nth term of an arithmetic sequence, you can use the formula: a_n = a_1 + (n-1)d, where a_n is the nth term, a_1 is the first term, n is the position of the term, and d is the common difference. In this case, the first term a_1 is 11 and the common difference d is 7. So, the nth term of this sequence is 11 + (n-1)7, which simplifies to 11 + 7n - 7, or 7n + 4.
The nth term is: 5-6n